What's happened to the humanities? - Kernan, Alvin B. (Princeton legacy library., 1997)
This volume of specially commissioned original essays presents the thoughts of some of the most distinguished commentators within the American academy on the fundamental changes that have taken place in the humanities in the latter part of the twentieth century. In the transformation of American higher education from the university to the "demoversity," the humanities have become a less and less important part of education, a matter established by a statistical appendix and elaborated on in several of the essays. The individual essays offer close observations into how the humanities have been affected by declining academic status, by demographic shifts, by reductions in financial support, and by changing communication technology. They also explore the effect of these forces on books, libraries, and the phenomenology of reading in the age of images. When basic conditions change, theory follows, and several essays trace the appearance and effect of new relativistic epistemologies in the humanities. Social institutions change as well in such circumstances, and the volume concludes with studies of the new social arrangements that have developed in the humanities in recent years: the attack on professionalism and the effort to transform the humanities into the social conscience of academia and even of the nation as a whole. Cause and effect? Who can say? What the essays make clear, however, is that as the humanities have become less significant in American higher education, they have also been the scene of unusually energetic pedagogical, social, and intellectual changes. The contributors to the volume are David Bromwich, John D'Arms, Denis Donoghue, Carla Hesse, Gertrude Himmelfarb, Lynn Hunt, Frank Kermode, Louis Menand, Francis Oakley, Christopher Ricks, and Margery Sabin. Included is a substantial introduction by Alvin Kernan and an appendix of tables and figures showing baccalaureate and doctoral degrees over the years in various types of schools. Originally published in 1997. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905